Key Challenges of Virtual Software Development Teams - Montonen, Jarno (2010)
Montonen, Jarno Johannes Key Challenges of Virtual Software Development Teams / Jarno Montonen Jyväskylä: Jyväskylä University, 2010. 41 p. Bachelor’s Thesis Many alleged benefits of virtual teams have motivated software companies to utilize virtual work in their projects. Building efficient virtual teams has, however, proven out to be a difficult task, and companies have found out that the alleged benefits may not always come true. To ease the efficient utilization of virtual teams in the future software development projects, this study researches virtual software development literature for key challenges that the teams face, as well as to find possible solutions to these challenges. The study found several key challenges and solutions for virtual software development teams and organized them into six categories. The results of this study help virtual team managers and personnel to acknowledge the state of their team in relation to the key challenges, as well as to understand how to improve the team’s chance for success and/or how to improve its performance. Additionally, the intuitive categorization presented makes it easier to understand and communicate the team’s issues.